International Capital Flows and Debt Dynamics - Evans, Martin (IMF Working Papers; Working Paper ;, 2012)
This paper presents a new model for studying international capital flows and debt dynamics that emphasizes the role played by expectations concerning future trade flows and returns. I use the model to estimate the drivers of the U.S. external position and capital flows between 1973 and 2008. The estimates show that most of the secular rise in U.S. international indebtedness is attributable to growing optimism about future returns on U.S. holdings of foreign equity and FDI assets. They also show that the transformation of world savings into risky assets by the U.S. had little effect on its external position, but the expected future real depreciation of the dollar allowed the U.S. to sustain a higher level of international debt after the 1990s.